DIDACTIC CONDITIONS OF CREATIVE FORMATION ACTIVITIES OF FUTURE TEACHERS IN THE SYSTEM PERSONALLY ORIENTED LEARNING (Pedagogy of Higher and Secondary Education, 2004)
The article exposes the didactic conditions according to which the process of forming students’ creative activity in personal-oriented system of education at higher pedagogical school.